E-Business maturity and information technology - Morais, Elisabete Paulo (2010)
Maturity models describe the maturing of the use of information systems in organizations. They are a useful framework to describe an organization’s current position as well as a range of possible position in the future in terms of their e-business maturity. The relationship between Information Technology (IT) and e-business maturity is examined. We used a model of e-business maturity, Stages Of Growth for e-business (SOGe) model, to put an organization in a maturity stage. In our survey we presented a set of technologies and we asked to enterprises which of them are implemented, in development, planned or inexistent. We concluded that there is a strongly correlation between IT implementation and the e-business maturity.